Susceptibility of Plutella xylostella (Lepidoptera: Plutellidae; Linnaeus 1758) to Beauveria bassiana Bb9205, Metarhizium anisopliae Ma9236 and Heterorhabditis bacteriophora HNI0100 - Correa, Jennifer Paola; Universidad Javeriana (2014)
The diamondback moth (Plutella xylostella) is a major pest of broccoli worldwide. It mainly causes leaf defoliation and generates annual losses of 80%. In this study we evaluated the susceptibility of P. xylostella to entomopathogens Heterorhabditis bacteriophora HNI0100, Beauveria bassiana Bb9205 and Metarhizium anisopliae Ma9236. The methodology was based on the inoculation of third instar larvae of P. xylostella with 5x101, 1x102, 3x102, 6x102 and 1,2x103 IJs/cm2 of H. bacteriophora HNI0100 and evaluated them after 24, 48 and 72 h and 1x104, 1x105, 1x106, 1x107 and 1x108 con/cm2 of B. bassiana Bb9205 and M. anisopliae Ma9236, which were evaluated during two weeks. At a dose of 1,2 x103 JIs/cm2, P. xylostella had a susceptibility to H. bacteriophora HNI0100 of 91,66%. Similarly, B. bassiana Bb9205 and M. anisopliae Ma9236 had a mortality of 95,33 and 99,67% at 1x105 con/cm2. The results suggest that the use of strains of entomopathogenic nematodes and fungi is an innovative alternative for the control of P. xylostella. However, studies on the interaction of nematodes and fungi and Plutella xylostella are necessary.